Athletes` opinions on food provision at European Athletics Championships: Implications for the future - Maldonado, I.; Oliveira, C. B.; Branco, P. A.; Sousa, M. (Nutrients, 2023)
In competitive events, athletes` performances can be affected by their food choices. In addition, nutrition labels are essential to sustain informed decisions and to allow athletes to comply with their dietary planning. Knowing what influences athletes` food choices will help to improve the food provision in future championships. Therefore, we aimed to study the factors influencing athletes` choices, their knowledge on nutrition labels, and their opinion on the food service at two European Athletics Championships. Questionnaires were completed by 339 athletes (57% males, 19.6 ± 1.3 years) competing at the 2019 European Athletics Under 20 and Under 23 Championships. Factors that may impact performance (time of the day and nutrient composition) were rated as important and very important by a higher percentage of athletes (78% and 74%, respectively) compared to the presence of teammates (32%) and the coach (23%). Among the athletes who knew what nutrition labels are (49%), 72% would like to have additional nutritional information in future championships. Furthermore, our study revealed that for most athletes (72%), food temperature is important or very important for food choices. Overall, food provision had positive results, but further research is needed to help organizers better tailor food provision to athletes` needs.